1993
DOI: 10.1007/bf02353718
|View full text |Cite
|
Sign up to set email alerts
|

Perceived parental characteristics of patients with obsessive compulsive disorder, depression, and panic disorder

Abstract: It has been hypothesized that parents of patients with obsessive compulsive disorder exhibit specific traits. 320 consecutive inpatient admissions who met criteria for OCD, depression, and panic disorder checked a list of adjectives to describe their parents. Patients with OCD were 1) less likely to perceive their mothers as disorganized than depressives, 2) more likely to perceive their mothers as overprotective than depressives and 3) less likely to perceive their fathers as demanding than patients with pani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The authors did not find a difference regarding perceived parental overprotection between the groups. This was surprising given the numerous studies describing high levels of parental overprotection in OCD patients (Merkel, Pollard, Wiener, & Staebler, 1993;Turgeon et al, 2002). One such study completed by Turgeon et al compared outpatients with panic disorder with agoraphobia (PDA), outpatients with OCD, and non-anxious controls.…”
Section: Parental Rearing Behaviorsmentioning
confidence: 93%
“…The authors did not find a difference regarding perceived parental overprotection between the groups. This was surprising given the numerous studies describing high levels of parental overprotection in OCD patients (Merkel, Pollard, Wiener, & Staebler, 1993;Turgeon et al, 2002). One such study completed by Turgeon et al compared outpatients with panic disorder with agoraphobia (PDA), outpatients with OCD, and non-anxious controls.…”
Section: Parental Rearing Behaviorsmentioning
confidence: 93%
“…A multivariate analysis of covariance, controlling for OCD severity, examined the FES subscales: Cohesion, Conflict, Control, and Organization. A multivariate effect was obtained (F (4,22) OCD ? Depression group reported significantly more Conflict and less Organization within the family compared to mothers of the OCD Alone group (See Table 5).…”
Section: Family Environmentmentioning
confidence: 99%
“…To date, no studies have differentiated family environments between children with depression and OCD. However, adult retrospective reports indicate that patients with OCD report that their mothers were more overprotective and more rigidly ''organized'' compared to patients with depression alone [22]. Increasing evidence suggests that family accommodation also plays a significant role in the maintenance of obsessions and compulsions [23,24].…”
mentioning
confidence: 98%
“…The result, according to Guidano and Llotti, is a rigid self-image that leads to needs for certainty and perfection. Findings from empirical evaluations of parental rearing style suggest that OCD patients perceive either or both of their parents to be less emotionally warm (Ehiobuche, 1988), overprotective (Merkel, Pollard, Wiener, & Staebler, 1993) and orderly and demanding (Steketee, Grayson, & Foa, 1987). Vogel, Stiles and Nordahl (1997) found that the recollections of OCD patients of parenting experiences did not differ from those of normal controls when depression was controlled for in analyses.…”
mentioning
confidence: 82%